Implementation of Pedagogic Competency of Islamic Religious Education Teachers to Improve the Quality of Students' Learning at Sman 7 Binjai - Khalistiasari, Rubi Yohana; Tumiran, Tumiran (Universitas Syiah Kuala, 2025)
The pedagogical competence possessed by teachers will make education the first step towards teacher success in educating students in school. This study aims to analyze the implementation of pedagogical competence that will be implemented by Islamic religious education teachers with the hope of being able to increase teacher competence by producing quality students with high, effective and efficient learning abilities. The research method used in this writing is a qualitative method with observation, interview and documentation data collection techniques. In this study, the informants were the principal / vice principal, Islamic Religious Education teachers and students at SMAN 7 Binjai. The results of this study are 1). Islamic Religious Education teachers at SMAN 7 Binjai carry out pedagogical competence quite well with efforts to improve the quality of student learning supported by the school by providing facilities for the development of effective, innovative and creative learning and teaching activities. 2). The teacher's pedagogical competence is implemented in accordance with the learning plan that has been prepared by the Islamic Religious Education teacher. 3). Students are very receptive to learning to be creative and improve their enthusiasm and quality of learning very well.